Response History Analysis for the Design of New Buildings in the NEHRP Provisions and ASCE/SEI 7 Standard: Part I - Overview and Specification of Ground Motions. Issue 2 (May 2017) - Haselton, Curt B.; Baker, Jack W.; Stewart, Jonathan P.; Whittaker, Andrew S.; Luco, Nicolas; Fry, Andy; Hamburger, Ronald O.; Zimmerman, Reid B.; Hooper, John D.; Charney, Finley A.; Pekelnicky, Robert G.
This manuscript, the first in a four-part series, describes the response history analysis approach developed for Chapter 16 of the ASCE/SEI 7 Standard and critical issues related to the specification of ground motions. Our approach provides new procedures for demonstrating adherence to collapse safety goals for new buildings (≤10% collapse probability at the MCER shaking level), creating nonlinear structural models, selecting and applying ground motions to the structural model, interpreting computed structural responses, and enforcing acceptance criteria to achieve the collapse safety goal. The ground motion provisions provide the option of using target spectra having more realistic spectral shapes than traditional uniform hazard spectra. Ground motions are developed using a two-stage procedure emphasizing spectral shape in their selection, followed by scaling or matching them to the target, with a modest penalty for matching. Horizontal component motions are applied to the structural model with random components to avoid bias associated with the maximum-component definition of the target spectrum.